Method for rapidly obtaining ultra-smooth surface through plasma and gadget combined process
Through the plasma and gadget combination process, the problem of traditional fused quartz glass processing method taking a long time and difficulty in controlling surface and subsurface defects is solved, and the effect of quickly obtaining ultra-smooth surfaces is achieved.
Patent Information
- Application Number
- CN202510205226.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-24
AI Technical Summary
The traditional fused quartz glass processing method takes dozens of hours to achieve ultrasmooth surfaces with surface shape errors less than 13 nm and surface roughness less than 0.2 nm, and it is difficult to control surface and subsurface defects.
The plasma and gadget combination process is used to remove the surface polymer deposition layer through the combination of plasma polishing and polyurethane polishing pads, and smooth the surface with asphalt tray widgets and cerium oxide abrasives to achieve the manufacturing of a lossless ultra-smooth surface.
The time for processing the lossless fused silica super smooth surface is significantly shortened, and the common convergence of surface shape error and roughness is achieved, and the lossless ultra smooth surface with a roughness Ra less than 0.20 nm is finally obtained.
Smart Images

Figure CN119839695A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of processing technology, and in particular relates to a method for quickly obtaining an ultra-smooth surface through a plasma and small tool combination process. Background Art
[0002] At present, the demand for high-quality optical components is increasing both at home and abroad, and optical manufacturing technology is also developing rapidly. Fused quartz is widely used in aerospace, telescopes, and lithography machines due to its high chemical stability and excellent optical transparency. The traditional processing method of fused quartz glass requires grinding, polishing, smoothing and other processes, and the polishing and shaping process requires cyclic iteration to achieve the simultaneous convergence of surface shape and roughness. This method takes more than dozens of hours to achieve an ultra-smooth surface with a surface error of less than 13 nm and a surface roughness of less than 0.2 nm, and surface and sub-surface defects are difficult to control.
[0003] For the fused quartz workpiece after grinding, commonly used processing methods include chemical etching, ion beam etching, plasma etching, etc. The chemical etching method uses HF acid to etch the components, but the etching process will cause the surface roughness to deteriorate rapidly, and the fine control of the etching process is difficult, and the stability of the etching amount is poor. Ion beam etching has high requirements for the initial surface quality, and there are problems of ion implantation and surface quality deterioration. The inductively coupled plasma (ICP) method has the advantages of high removal efficiency and no surface and subsurface damage. The possible polymer deposition contamination problem can be effectively suppressed by the residence time trisection method, and the hardness of the polymer is lower than that of the fused quartz substrate, so the polymer can be removed preferentially in the process of smoothing with the use of a small tool. The present invention can give full play to the advantages of plasma fast and non-destructive shaping, shorten the processing time, and cooperate with the asphalt disk small tool to reduce the surface roughness while maintaining the surface shape, thereby improving the manufacturing efficiency of non-destructive ultra-smooth surfaces. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for quickly obtaining an ultra-smooth surface by combining a plasma and a small tool process, which can quickly process the fused quartz glass after cutting, forming and rough grinding into a lossless ultra-smooth surface. First, the fused quartz glass after cutting, forming and rough grinding is subjected to plasma polishing, and a total residence time segmented superposition process is adopted to achieve rapid removal of the fused quartz surface material and suppress the thickness of the polymer deposition layer. A polyurethane polishing pad is used in the middle. After removing the surface polymer, the plasma process parameters are adjusted and the RMS of the fused quartz surface shape error is converged to less than 12nm without sub-surface damage. After cleaning, an asphalt disk small tool is used in combination with cerium oxide abrasive to achieve smooth fused quartz surface. The present invention can significantly shorten the time for lossless ultra-smooth surface processing of fused quartz, achieve the common convergence of surface shape error and roughness, and finally obtain a lossless ultra-smooth surface with a roughness Ra less than 0.20 nm.
[0005] Small tool polishing refers to the process of finishing the workpiece surface using small polishing tools, which is a special term.
[0006] In order to achieve the above object, the present invention adopts the following technical scheme:
[0007] A method for quickly obtaining an ultra-smooth surface by combining a plasma and a small tool process comprises the following steps:
[0008] Step 1: Plasma processing of the ground fused quartz workpiece;
[0009] Step 2: Calculate the residence time T of each point in the grating trajectory through the plasma removal function and the volume to be removed;
[0010] Step 3: Use a polyurethane polishing pad with 2μm cerium oxide abrasive to remove the surface polymer deposition layer;
[0011] Step 4: Enter the shaping stage, adjust the plasma process parameters, reduce the removal amount, so as to achieve fine shaping, and finally obtain a lossless ultra-smooth surface with a surface error RMS less than 13 nm;
[0012] Step 5: Cleaning, then rinsing with deionized water, and finally drying on a clean bench to obtain a fused quartz component that has been ultrasonically cleaned after plasma processing;
[0013] Step 6: Use an asphalt disc tool with cerium oxide abrasive for smoothing, and use gradient pressure for 3 times;
[0014] Step 7: Clean again, then rinse with deionized water and dry on a clean bench. Finally, use a transmission electron microscope to observe the subsurface damage and use a white light interferometer to measure the surface roughness. Finally, a lossless ultra-smooth surface with a surface roughness better than 0.20 nm is obtained.
[0015] Furthermore, in step 1, the plasma used is generated by an inductively coupled plasma device, and the front process of the processed fused quartz workpiece forms a rough surface after grinding and forming.
[0016] Furthermore, in step 1, the plasma processing parameters are set as follows: power is 350 W, gas flow rate is 15 sccm, and processing spacing is 12 mm.
[0017] Furthermore, in step 2, the dwell time trisection method is to divide the dwell time of each point into three equal parts to generate three processing trajectories to suppress the influence of the accumulated temperature change during the processing on the deposition thickness of the plasma processed polymer and remove the surface and sub-surface damage caused by the previous process.
[0018] Furthermore, in step 3, a φ10 mm polyurethane polishing pad with a cross groove is used, which is beneficial to the storage and renewal of abrasive particles during the polishing process and improves the stability of material removal. The polishing pressure is 25N, the revolution speed is 120 rand / min, the rotation speed is 100 rand / min, the eccentricity is 3 mm, and one processing is sufficient.
[0019] Furthermore, in step 4, the plasma power is 320 W, the gas flow rate is 18, and the processing spacing is 15.
[0020] Furthermore, in step 5, the orbital and rotational speeds and eccentricity used are process parameters obtained after optimization.
[0021] Furthermore, in step 6, a small asphalt disc tool with a diameter of 10 mm is selected, with an orbital speed of 110 rand / min, a rotation speed of 50 rand / min, and an eccentricity of 3 mm.
[0022] Furthermore, in step 6, a cerium oxide polishing liquid with an average particle size of 200-300 nm is used, the processing track is also a grating track, and gradient pressure is used for three processings, and the pressure loads are 8 N, 6 N, and 4 N respectively.
[0023] Furthermore, in step 7, the cleaning process requires using an isopropyl alcohol jet to clean the surface of the workpiece.
[0024] The beneficial effects of the present invention are:
[0025] The present invention is based on the problem that the chemical etching process is difficult to finely control, the etching amount is poorly stable, and the problems of ion injection and surface quality deterioration in ion beam etching. The inductively coupled plasma (ICP) method has the advantages of high removal efficiency and no surface and subsurface damage. The possible polymer deposition contamination problem can be effectively suppressed by the residence time trisection method. Since the hardness of the polymer is lower than that of the fused quartz substrate, the polymer can be removed preferentially in the process of smoothing with the use of a small tool. The present invention can give full play to the advantages of plasma fast and non-destructive shaping, shorten the processing time, and cooperate with the asphalt disk small tool to reduce the surface roughness while maintaining the surface shape, thereby improving the manufacturing efficiency of non-destructive ultra-smooth surfaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A flow chart of a method for rapidly obtaining an ultra-smooth surface by a plasma and small tool combination process of the present invention;
[0027] Figure 2 Schematic diagram of the principle of obtaining a lossless surface by ICP plasma;
[0028] Figure 3 Schematic diagram of the asphalt disc gadget processing equipment and material removal mechanism;
[0029] Figure 4 A graph showing the distribution of abrasive particles used in the smoothing process;
[0030] Figure 5 The actual picture of the surface changes during the processing; 1 is the initial grinding and forming surface, 2 is the surface after plasma processing, 3 is the surface after polyurethane removal of polymer deposition, and 4 is the surface after fine shaping and smoothing;
[0031] Figure 6 The laser interferometer and white light interferometer respectively measure the surface shape error and roughness results;
[0032] Figure 7 Results of subsurface damage detection using transmission electron microscopy. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0034] like Figure 1As shown, the present invention provides a method for quickly obtaining an ultra-smooth surface by combining a plasma and a small tool process, comprising the following steps:
[0035] Step 1: Plasma processing is performed on the ground fused quartz workpiece. Since the ground surface is rough and has deep subsurface damage, a large amount of removal is required.
[0036] Preferably, the plasma processing parameters are set to a power of 350 W, a gas flow rate of 15 sccm, and a processing spacing of 12 mm.
[0037] Step 2: Calculate the residence time T of each point in the grating trajectory through the plasma removal function and the volume to be removed.
[0038] Step 3: Since the polymer deposition of plasma will affect the further removal of the material on the workpiece surface, a polyurethane polishing pad with 2 μm cerium oxide abrasive is used to remove the surface polymer deposition layer;
[0039] Step 4: Enter the shaping stage, adjust the plasma process parameters, and reduce the removal amount to achieve fine shaping.
[0040] Preferably, the plasma power is 320 W, the gas flow rate is 18, the processing spacing is 15, and finally a lossless ultra-smooth surface with a surface error RMS less than 13 nm is obtained;
[0041] Step 5: Cleaning, then rinsing with deionized water, and finally drying on a clean bench to obtain a fused quartz component that has been ultrasonically cleaned after plasma processing;
[0042] Preferably, the cleaning is ultrasonic cleaning in anhydrous ethanol at 20° C. for 3 to 5 minutes.
[0043] Step 6: Use an asphalt disc tool with cerium oxide abrasive for smoothing.
[0044] Step 7: Clean again, then rinse with deionized water and dry on a clean bench. Finally, use a transmission electron microscope to observe the subsurface damage and use a white light interferometer to measure the surface roughness. Finally, a lossless ultra-smooth surface with a surface roughness better than 0.20 nm is obtained.
[0045] Preferably, the second cleaning is to use a 25° C. isopropanol jet to clean the additive residue in the polishing liquid, followed by ultrasonic cleaning in anhydrous ethanol at 20° C. for 3 to 5 minutes.
[0046] Furthermore, in step 1, the plasma used is an inductively coupled plasma (ICP) device, and the previous process of processing the fused quartz workpiece is grinding the rough surface after forming.
[0047] Furthermore, in step 2, the dwell time trisection method is to divide the dwell time of each point into three equal parts to generate three processing trajectories to suppress the influence of the accumulated temperature change during the processing on the deposition thickness of the plasma processed polymer and remove the surface and sub-surface damage caused by the previous process.
[0048] Preferably, since a single-point plasma residence time that is too long will produce polymer deposition on the fused quartz surface and affect the surface quality, the thickness of the polymer can be significantly suppressed by dividing the residence time of the residence point into three equal parts, that is, while keeping the total residence time unchanged, walking the grating track three times, with the residence time of each time being 1 / 3 T.
[0049] Furthermore, in step 3, the φ10 mm polyurethane polishing pad used has a cross groove, which is beneficial to the storage and renewal of abrasive particles during the polishing process and improves the stability of material removal. The polishing pressure is 25N, the revolution speed is 120 rand / min, the rotation speed is 100 rand / min, the eccentricity is 3 mm, and one processing is sufficient.
[0050] Furthermore, in step 6, the orbital speed and eccentricity used are process parameters obtained after optimization. Since the relative speed of the center position of the rotating axis is 0 during the rotation of the small tool, material removal cannot be achieved, so it is necessary to increase the relative speed through revolution and promote the renewal of abrasive particles.
[0051] Preferably, a small asphalt disk tool with a diameter of 10 mm is selected, the orbital speed is 110 rand / min, the rotation speed is 50 rand / min, the eccentricity is 3 mm, and a cerium oxide polishing liquid with an average particle size of 200-300 nm is used. The processing trajectory is also a grating trajectory, and gradient pressure is used for three processings, and the pressure loads are 8 N, 6 N, and 4 N respectively.
[0052] The average particle size of cerium oxide polishing liquid used is 200-300 nm, which is measured by Malvern particle size analyzer. Since cerium oxide abrasive particles are irregular polyhedrons with sharp edges and corners, they are easy to damage the surface, so it is necessary to use cerium oxide abrasive particles with small particle size and concentrated distribution.
[0053] In step 6, the pressure gradient processing method can remove polymer deposits that may exist on the surface when the pressure is relatively high in the first pass, and the subsequent pressure decreases to reduce the average load of effective abrasive particles in the polishing liquid, thereby promoting the removal of materials by mechanically inducing chemical bond breaking of the abrasive particles, thereby improving the overall processing efficiency and obtaining a lossless ultra-smooth surface.
[0054] Furthermore, in step 7, the cleaning process needs to use an isopropyl alcohol jet to clean the workpiece surface, because chemical additives are required in cerium oxide abrasives to improve the dispersibility and stability of abrasive particles, and isopropyl alcohol can remove organic solvents that may remain on the surface. Subsequently, anhydrous ethanol and deionized water are used for cleaning, and finally drying is performed.
[0055] Example:
[0056] The embodiment of the present invention provides a method for quickly obtaining an ultra-smooth surface by combining a plasma and a small tool process, comprising the following steps:
[0057] Step 1: The ground fused quartz workpiece of φ50×5mm is processed using an inductively coupled plasma (ICP) device. The material removal process is as follows: Figure 2 As shown in the figure, the traditional optical component processing process from blank to finished product needs to go through the process flow of rough grinding, fine grinding, rough polishing and fine polishing. Since the surface of the ground blank is rough and there is deep sub-surface damage, a large amount of removal is required. The plasma processing parameters are set to 350W power, 15 sccm gas flow, 12mm processing spacing, and the workpiece is fixed to the workbench. Under the action of plasma, sub-surface damage, such as cracks, will first undergo a crack opening process, and plasma etching pits will gradually appear on the surface. As time accumulates, the etching pits continue to extend and merge until the damaged layer is completely removed, and finally a damage-free surface is obtained.
[0058] Step 2: The total dwell time of the grating track is calculated to be 60 minutes through the plasma removal function and the volume to be removed. By dividing the dwell time of the dwell point into three equal parts, that is, walking the grating track three times with a dwell time of 20 minutes each while keeping the total dwell time constant, the thickness of the polymer can be significantly suppressed, and the surface and subsurface damage caused by the previous process can be removed;
[0059] Step 3: Since the polymer deposition of plasma will affect the further removal of the material on the workpiece surface, a polyurethane polishing pad with 2μm cerium oxide abrasive is used to remove the surface polymer deposition layer. The φ10 mm polyurethane polishing pad used has a cross groove, which is conducive to the storage and renewal of abrasive particles during the polishing process and improves the stability of material removal. The polishing pressure is 25N, the revolution speed is 120 rand / min, the rotation speed is 100 rand / min, the eccentricity is 3 mm, and the processing time is 40 minutes.
[0060] Step 4: Enter the fine shaping stage, adjust the plasma process parameters, reduce the removal amount, and achieve fine shaping. The power is 320W, the gas flow rate is 18, and the processing interval is 15. The processing program is regenerated according to the surface shape after each processing. It is iterated 3 times, each processing is 10 minutes, and the total processing time is 30 minutes. Finally, a lossless ultra-smooth surface with a surface shape error RMS less than 13 nm is obtained.
[0061] Step 5: Ultrasonic cleaning in anhydrous ethanol at 20°C for 3-5 minutes, followed by rinsing with deionized water, and finally drying on a clean bench to obtain a fused quartz component that has been ultrasonically cleaned after plasma processing;
[0062] Step 6: Use an asphalt disc tool with cerium oxide abrasive for smoothing. The processing equipment and material removal mechanism are as follows: Figure 3 As shown, the fused quartz workpiece is fixed to the workbench, and the asphalt disk tool acts on the surface of the fused quartz workpiece with a certain load while performing radial and rotational motions. Since the hardness of the polymer deposit generated by the plasma is less than that of the fused quartz, the abrasive particles at the polishing interface preferentially remove the polymer deposits on the surface, and ultimately achieve ultra-smooth processing to obtain an ultra-smooth surface.
[0063] Select a small asphalt disk tool with a diameter of 10 mm, a revolution speed of 110 rand / min, a rotation speed of 50 rand / min, an eccentricity of 3 mm, and use a cerium oxide polishing liquid with an average particle size of 200-300 nm. The particle size distribution test results are as follows Figure 4 As shown in the figure, the average particle size is 236.4 nanometers, the processing trajectory is also a grating trajectory, and gradient pressure is used for three processings, with pressure loads of 8 N, 6 N, and 4 N respectively. When the pressure is high in the first pass, the polymer deposition that may exist on the surface can be removed. The subsequent pressure decreases to reduce the average load of effective abrasive particles in the polishing liquid, and promotes the removal of materials by mechanically inducing chemical bond breaking of the abrasive particles. The overall processing efficiency can be improved while obtaining a non-destructive ultra-smooth surface. Each processing time is 40 minutes.
[0064] Step 7: Clean again, use 25℃ isopropyl alcohol jet to clean the additive residue in the polishing liquid, then ultrasonically clean in 20℃ anhydrous ethanol for 3~5 minutes, then rinse with deionized water and dry on the clean bench. The surface changes during the processing are as follows: Figure 5 As shown ( Figure 5 1 is the initial grinding and forming surface, Figure 5 2 is the surface after plasma processing, Figure 5 3 is the surface after polyurethane removal polymer deposition, Figure 5 4 is fine shaping and smooth rear surface;
[0065] It can be clearly found that the surface of the fused quartz workpiece changes from the initial rough surface to a bright surface. Finally, the surface shape error and roughness are measured using a laser interferometer and a white light interferometer, respectively. Figure 6 As shown in Figure 2, although the surface error has slightly deteriorated by 10.7%, the roughness has decreased by 89.8%. The subsurface damage was observed using a transmission electron microscope, and the test results are as follows: Figure 7 shown.
[0066] Compared with the traditional processing process, the entire processing process only takes about 250 minutes to transform a φ50×5mm fused quartz workpiece from a ground rough surface to a lossless ultra-smooth surface with a surface error of less than 13nm and a surface roughness better than 0.20nm, reducing time costs and achieving efficient processing of the ultra-smooth surface of fused quartz.
Claims
1. A method for quickly obtaining an ultra-smooth surface by combining a plasma and a small tool process, characterized in that: The steps include: Step 1: Plasma processing of the ground fused quartz workpiece; Step 2: Calculate the residence time T of each point in the grating trajectory through the plasma removal function and the volume to be removed; Step 3: Use a polyurethane polishing pad with 2μm cerium oxide abrasive to remove the surface polymer deposition layer; Step 4: Enter the shaping stage, adjust the plasma process parameters, reduce the removal amount, so as to achieve fine shaping, and finally obtain a lossless ultra-smooth surface with a surface error RMS less than 13 nm; Step 5: Cleaning, then rinsing with deionized water, and finally drying on a clean bench to obtain a fused quartz component that has been ultrasonically cleaned after plasma processing; Step 6: Use an asphalt disc tool with cerium oxide abrasive for smoothing, and use gradient pressure for 3 times; Step 7: Clean again, then rinse with deionized water and dry on a clean bench. Finally, use a transmission electron microscope to observe the subsurface damage and use a white light interferometer to measure the surface roughness. Finally, a lossless ultra-smooth surface with a surface roughness better than 0.20 nm is obtained.
2. The method for rapidly obtaining an ultra-smooth surface by combining a plasma and a small tool process according to claim 1, characterized in that: In the step 1, the plasma used is generated by an inductively coupled plasma device, and the front process of the processed fused quartz workpiece forms a rough surface after grinding and forming.
3. The method for rapidly obtaining an ultra-smooth surface by combining a plasma and a small tool process according to claim 1, characterized in that: In step 1, the plasma processing parameters are set as follows: power is 350 W, gas flow rate is 15 sccm, and processing spacing is 12 mm.
4. The method for rapidly obtaining an ultra-smooth surface by combining plasma and small tooling according to claim 1, characterized in that: In step 2, the dwell time trisection method is to divide the dwell time of each point into three equal parts to generate three processing trajectories to suppress the influence of the accumulated temperature change during the processing on the deposition thickness of the plasma processed polymer and remove the surface and sub-surface damage caused by the previous process.
5. The method for rapidly obtaining an ultra-smooth surface by combining plasma and small tooling according to claim 1, characterized in that: In step 3, a φ10 mm polyurethane polishing pad with a cross groove is used, which is beneficial to the storage and renewal of abrasive particles during the polishing process and improves the stability of material removal. The polishing pressure is 25N, the revolution speed is 120 rand / min, the rotation speed is 100 rand / min, and the eccentricity is 3 mm.
6. The method for rapidly obtaining an ultra-smooth surface by combining a plasma and a small tool process according to claim 1, characterized in that: In step 4, the plasma power is 320 W, the gas flow rate is 18, and the processing spacing is 15.
7. The method for rapidly obtaining an ultra-smooth surface by combining a plasma and a small tool process according to claim 1, characterized in that: In step 5, the orbital and rotational speeds and eccentricity used are process parameters obtained after optimization.
8. The method for rapidly obtaining an ultra-smooth surface by combining a plasma and a small tool process according to claim 1, characterized in that: In step 6, a small asphalt disk tool with a diameter of 10 mm is selected, with an orbital speed of 110 rand / min, a rotation speed of 50 rand / min, and an eccentricity of 3 mm.
9. The method for rapidly obtaining an ultra-smooth surface by combining plasma and small tooling according to claim 1, characterized in that: In step 6, a cerium oxide polishing liquid with an average particle size of 200-300 nm is used, the processing track is also a grating track, and gradient pressure is used for three times, and the pressure loads are 8 N, 6 N, and 4 N respectively.
10. The method for rapidly obtaining an ultra-smooth surface by combining plasma and small tooling according to claim 1, characterized in that: In step 7, the cleaning process requires using an isopropyl alcohol jet to clean the surface of the workpiece.
Citation Information
Patent Citations
Ultra-precise grinding head and using method thereof
CN105290916A
Plane optical element and machining method thereof
CN110682165A
Combined processing technology for fused quartz optical surface ultra-smooth processing
CN110877255A
Plasma source and surface treatment method
US20170137939A1